Sized-related changes in winter condition of male calves in reindeer - Helle, T.; Pulliainen, E.; Aspi, J. (Rangifer, 1987)
Size-related changes in body condition of free-ranging male calves of semi-domesticated reindeer were studied in northern Finland from October 1983 to February 1984. In October-November, back fat depth or muscle fat percent correlated positively with the body size (=back length). In January, the highest means especially for muscle fat percent were found among medium-sized calves. Carcass weight and weight/back length ratio correlated positively with size, excluding February sample, where correlation for carcass weight was non-significant and for weight/back length ratio negative. Weight in the autumn correlated negatively with weight in February. Therefore, normalizing selection for body size (working against small and large phenotypes) is expected to occur in late winter. Small calves may be at greater mortality risk because of lower initial body reserves. Large calves commonly disperse during the rutting season and they may suffer most from increased food competition later in winter. Using of medium-sized calves for breeding might be the safest policy on ranges characterized by short food supply and difficult snow conditions. Koon vaikutus poron urosvasojen talviseen kuntoon. Abstract in Finnish / Tiivistelmä: Koon vaikutusta vapaana laiduntavien poron urosvasojen kuntoon tutkittiin Pohjois-Suomessa loka-helmikuussa talvella 1983-84. Loka-marraskuussa selkärasvan paksuus tai lihaksen rasvaprosentti riippui vasan koosta ( = selän pituus). Tammikuussa sen sijaan lihaksen rasvaprosentti oli korkein keskikokoisilla vasoilla. Ruhopaino sekä ruhopaino/selän pituus oli yleensa riippuvainen koosta. Helmikuussa ruhopainon riippuvuus koosta ei ollut enää tilastollisesti merkitsevä, ja koon ja ruhopainon/selänpituuden välinen korrelaatio oli negatiivinen. Eniten painoa menettivät (%) loka-helmikuun välillä suurikokoisimmat vasat. Havainnot viittaavat siihen, että talvella esiintyvä kuolleisuus on normalisoivaa koon suhteen (karsii pieniä ja suuria fenotyyppejä). Pienten vasojen kuolleisuusriski on suuri alunperinkin vähäisen varastoravinnon vuoksi. Suuret vasat puolestaan erkaantuvat usein emistään jo rykimäaikana, ja joutuvat kärsimään eniten talven mittaan kiristyvästä ravintokilpailusta. Niukoilla laitumilla siitokseen on turvallisinta säästää keskikokoisia vasoja. Sammenhengen mellom størrelse og vinterkondisjon hos hankalver av reinsdyr. Abstract in Norwegian / Sammendrag: Størrelses-relaterte forandringer i kroppskondisjon hos fritt beitende han-kalver av semidomestiserte rein er studert i Nord-Finland fra oktober 1983 til februar 1984. I oktober - november korrelerte tykkelsen av ryggfettet eller muskelfett-prosenten positivt med kroppsstørrelsen (= rygglengden). I januar ble de høyeste middelverdier, særlig for muskelfett-prosenten, funnet hos kalver av middels størrelse. Skrott-vekter og vekt/rygglengde-forholdet korrelerte positivt med kroppsstørrelse bortsett fra februar-prøvene, der korrellasjonen for skrott-vekt var ikke-signifikant og for vekt/rygglengde-forholdet var negativt. Vekt om høsten korrelerte negativt med vekt i februar. Derfor ventes et normaliserende utvalg for kroppsvekt (som arbeider mot små og store fenotyper) å skje på senvinteren. Små kalver er utsatt for større dødsrisiko på grunn av lavere kroppsreserver. Store kalver streifer vanligvis under brunsttiden og kan komme til å lide under økt næringskonkurranse på senvinteren. Bruk av middels store kalver i avlen kan være den sikreste metode på beiter som karakteriseres av dårlige næringstilgang og vanskelige snøforhold.